Protecting hidden treasures: Indigenous lands safeguard 50% of areas with the highest potential for angiosperm discoveries in Brazil—patterns and conservation priorities - Janaína Gomes-da-Silva; Eimear Nic Lughadha; Rafaela Campostrini Forzza (PLoS ONE, 2025)
Brilliantly adapted from aphorist and geneticist Dobzhansky’s phrase, “Nothing in biology makes sense except in the light of taxonomy” conveys the fact that various scientific fields depend on correctly identified and accurately described species. In this sense, estimating the number of extant species is one of the fundamental issues and has direct implications for biodiversity conservation. Worldwide, approximately 370,000 angiosperm species are known to science; however, studies indicate that another ~100,000 or as many as 315,000 are yet to be described for science. Brazil is recognized for its megabiodiversity and currently recognizes 32,900 native species of angiosperms. What would be the impact on conservation priorities if all undescribed species were known and the catalog was complete? To explore this, we analyzed datasets of taxonomic information available for Brazilian angiosperms published between 1753 and 2020 to understand patterns of species discovery and identify which areas in which Brazilian phytogeographic domains harbor the largest number of species unknown to science. The likely number of species remaining to be described was extrapolated using predictive models and incorporating taxonomic effort over time. We estimated that the catalog of Brazilian angiosperms is at least 19–23% incomplete, with the proportion incomplete ranging from 4% to 39% across phytogeographic domains, and 7343–9595 species still awaiting description. Despite differences between models, overall trends consistently indicate the Amazonia and Caatinga regions offer greatest potential for new species descriptions. Our analysis revealed that human population density explains more variation in rates of angiosperm description over centuries than taxonomic effort, but taxonomic effort is a better predictor of recent description rates. Worryingly, 80% of areas predicted to be richest in undescribed angiosperm species do not overlap with protected areas (PAs), but 50% are within Indigenous lands. These findings highlight the urgent need to expand collection efforts and PAs coverage, particularly in the Caatinga, which has low levels of protection, and in Amazonia, where collaboration with indigenous communities is crucial for biodiversity conservation. Without direct action, many undescribed species and their undocumented traits and potential may be lost.